Collaborative registered replication of Griskevicius et al. (2010): can pro-environmental behavior be promoted by priming status motivation? - Lazarevic, Ljiljana; Wagge, Jordan R.; Balci, Busra Bahar; Buchanan, Erin M.; Greene, Nathaniel R.; Folwarczny, Michał; Lazić, Aleksandra; Want, Stephen C.; Lee, Seungyeon; Raddatz, Megan C.; Hehman, Eric; Gentile, Adriana; et al. (Collabra: Psychology, 2025)
The present study presents the results of a collaborative registered replication of Griskevicius et al. (2010, Experiment 1). As part of the Collaborative Replication and Education Project, 24 student groups from six countries (N = 3,774) investigated whether pro-environmental behavior can be promoted by priming status motives (desires for social status and prestige). This large, multi-site replication showed no evidence to support the hypothesis that hypothetical pro-environmental behavior can be stimulated by having participants read a story designed to prime status motives. We performed several exploratory analyses to investigate whether extension variables (i.e., equating “green” choices with prosocial behavior, political beliefs, sampling methods, location, duration of data collection, and gender) moderated the hypothesized effect of status motives on pro-environmental choices, but these analyses produced null results. One limitation of the study is that most data collection sites did not include a manipulation check, and the one site that did found a much weaker effect (d = 0.32) than the extremely large effect originally reported (d = 3.69). As a result, it remains unclear whether the null result reflects a failure of this specific priming method or a challenge to the underlying theory.
Gesehen am 20.01.2026